(3GdETQGa Ydi eYQaI GdCWQGas - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3YHjO Gddg Hf YHO Gddg Hf YeQ Hf GdNWGH GdYOhi GdeOfi Yf CHj gQjQI MOjK ajef CUHM LfHG ai QeVGf s
(3BNQgG (B:s
(3gPG BNQ cJGH CWQGa gPg GdcJH s
(3Ydi dhMI GdYfhGf JedcGJs
(3ai BNQ GdfSNI KdGK hQbGJ HgG CSGfjO GdeUfa Edi cJH GdCWQGas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B103s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdMOjK h GdeUWdMs